2017
DOI: 10.1155/2017/8271376
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of On‐Pump and Off‐Pump Bypass Operations on Oxidative Damage and Antioxidant Parameters

Abstract: Objective The aim of the study is to determine the oxidative status in on-pump and off-pump coronary artery surgery and contribute to possible surgical choices in clinical practices in accordance with the information obtained as a result of this study. Methods 52 patients undergoing open heart surgery (26 patients in on-pump group and 26 patients in off-pump group) were included in the study. MDA, GPx, GSH, CAT, and SOD were investigated in blood samples. Results In the on-pump group, it was determined that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
(39 reference statements)
1
11
0
1
Order By: Relevance
“…An intragroup analysis has indicated that the postoperative CAT level of Group 1 significantly increased compared to the preoperative level. Conforming to a previous study, 27 the postoperative CAT level of Group 2 in our study significantly decreased compared with its preoperative level. In a study in which a continuous mechanical ventilator strategy was used, the thiol and native thiol levels were significantly higher at 24 hours postoperatively than those of patients who were not ventilated.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…An intragroup analysis has indicated that the postoperative CAT level of Group 1 significantly increased compared to the preoperative level. Conforming to a previous study, 27 the postoperative CAT level of Group 2 in our study significantly decreased compared with its preoperative level. In a study in which a continuous mechanical ventilator strategy was used, the thiol and native thiol levels were significantly higher at 24 hours postoperatively than those of patients who were not ventilated.…”
Section: Discussionsupporting
confidence: 87%
“…However, no significant differences were found in the postoperative period. 27 In groups 1 and 2 of our study, the changes from the preoperative period to the postoperative period were minimal and not significant. Conversely, the intraoperative and postoperative MDA levels of Group 3 were significantly higher than the preoperative levels.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…It has been established that patients with hyperlipidemia have impaired antioxidant defense systems. According to previous studies, superoxide dismutase and glutathione peroxidase activities in hyperlipidemic patients have been demonstrated to be significantly lower than that in normolipidemic patients ( 26 ). Therefore, it is reasonable to attribute the higher MDA levels in hyperlipidemic patients to impaired or weak oxidative stress defense system.…”
Section: Discussionmentioning
confidence: 93%
“…Malondialdehyde (MDA) is considered as one of the most indicators of oxidative stress and damage produced as a result of lipid peroxidation, also the same author recorded an increase in the level of MDA in the early postoperative stage as an indicator of reperfusion damage that occurs immediately after open-heart surgery. According to Dogan and Turker (2017) showed an excessive production of free radicals mainly in open-heart surgery leading to an increase in oxidative stress systemically which is commonly related to the higher production of MDA. Arif et al (2019)…”
Section: Statistical Data In Tables (mentioning
confidence: 99%